Influence of Secondary School Inspection on Lesson Planning in Western Uganda - Bagaya, Jerry; Ezati, Betty Akullu; Wafula, Wycliffe Scot; Rasmussen, Palle (Journal of Education and Practice, 2020)
School inspection is one of the leading factors in attaining better pedagogy including lesson planning. To that end, any attempt to improve the quality of lesson planning should be given the attention it deserves. This paper, therefore, examines how and to what extent inspection influences teachers’ lesson planning in secondary schools in Western Uganda. A concurrent triangulation mixed methods research design involving questionnaire survey and interview, with a total of 399 participants in the categories of school inspectors, teachers, head teachers, and deputy headteachers from 36 secondary school in Western Uganda, was adopted. Quantitative data were analysed using frequencies, ratios and Linear Regression Analysis, while qualitative data were analysed using Qualitative Content Analysis. The study revealed that inspection did not significantly influence lesson planning in secondary schools. The study concluded that inspection has not contributed to improving lesson planning in secondary schools in Uganda. The research advances theory on inspection by demonstrating that merely visiting schools to conduct inspections does not necessarily lead to improvement in lesson planning. Improvement rather hinges on the ways that inspectors communicate, with teachers, prior, during and after the inspection. Understanding teachers’ beliefs, practices, and perceptions is important for improving educational processes.
Keywords: Inspection, lesson planning, secondary schools, Uganda